Computer-Aided Diagnostics of Human Arterial System - Klara Capova; Ivo Cap; Vladimir Blazek; Lydia Buckuliakova (Advances in Electrical and Electronic Engineering, 2003)
The paper deals with the modelling and the simulation of physiological fluid systems laying emphasise on the human vascular system. The presented simulation method has been developed as a helpful tool for the computer-aided non-invasive diagnostics of living bodies. Using the electromechanical analogy between physiological and electrical values the introduced method makes possible the description and 3D representation of the non-linear characteristics of the human haemodynamics as well. The simulation procedure and the obtained results verified by the experiment enable to visualize all physiological and pathophysiological states of the human vascular system.